Performance changes during a weeklong high-altitude alpine ski-racing training camp in lowlander young athletes - Hydren, J. R.; Kraemer, W. J.; Volek, J. S.; Dunn-Lewis, C.; Comstock, B. A.; Szivak, T. K.; Hooper, D. R.; Denegar, C. R.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2013)
Thousands of youth athletes travel to high altitude to participate in lift-access alpine sports. The purpose of this study was to examine the impact of acute high-altitude exposure on balance, choice reaction time, power, quickness, flexibility, strength endurance, and VO2max in youth lowlander athletes during a weeklong preseason training camp in Summit County, CO, USA. Eleven youth ski racers (4 boys and 7 girls; age, 13.7 ± 0.5 years; height, 157.2 ± 12.6 cm; weight, 52.4 ± 6.8 kg) with 7.7 ± 2.2 skiing years of experience participated in baseline testing at 160 m one week before the camp and a set of daily tests in the morning and afternoon at 2,828 m and skied between 3,328 and 3,802 m during a 6-day camp. Balance and choice reaction time tests were stagnant or improved slightly during the first 3 days and then improved on days 4 and 6. Vertical jump, flexibility, T-agility test, and push-ups in 1 minute improved on day 6. The number of sit-ups in 1 minute did not improve, and scores on the multistage fitness test decreased 20.34%. There was no effect of Lake Louise acute mountain sickness (AMS) questionnaire scores on performance variables measured. Athletes sojourning to high altitude for ski camps can train on immediate ascent but should slowly increase training volume over the first 3 days. Athletes should expect improvements in balance and reaction time 3-6 days into acclimatization. Coaches and athletes should expect about 20% of youth lowlander athletes to have signs and symptoms of AMS during the first 3 days of altitude exposure for alpine lift access sports at altitudes of up to 3,800 m.